2021
DOI: 10.3390/su13179895
|View full text |Cite
|
Sign up to set email alerts
|

School Failure in the Region of Madrid (Spain): An Approximation through Diagnostic Assessment in 2019

Abstract: Education is considered to be one of the main factors of development, economic growth and social progress. No country can achieve sustainable economic development without substantial investment in human capital. In Spain, school failure represents one of the main problems in the educational system, with potentially dramatic consequences for the basic competences required in the labour market and job instability, with the risk of economic and social exclusion. In this paper, we aim to identify the factors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…The results it yields can offer preliminary evidence of the effectiveness of a developed test in capturing students' misconceptions and evaluating their understanding of science concepts (Soeharto, 2021). Diagnostic assessments also play a crucial role in identifying potential learning difficulties, particularly among learners in disadvantaged socioeconomic circumstances who are at a higher risk of academic underachievement (Pires et al, 2021). Moreover, diagnostic assessments alleviate the stress of the academic literacy acquisition process for many first-year students and underscore the potential benefits of incorporating such assessments for enhancing retention and engagement (Palmer et al, 2018).…”
Section: Institutionsmentioning
confidence: 99%
“…The results it yields can offer preliminary evidence of the effectiveness of a developed test in capturing students' misconceptions and evaluating their understanding of science concepts (Soeharto, 2021). Diagnostic assessments also play a crucial role in identifying potential learning difficulties, particularly among learners in disadvantaged socioeconomic circumstances who are at a higher risk of academic underachievement (Pires et al, 2021). Moreover, diagnostic assessments alleviate the stress of the academic literacy acquisition process for many first-year students and underscore the potential benefits of incorporating such assessments for enhancing retention and engagement (Palmer et al, 2018).…”
Section: Institutionsmentioning
confidence: 99%
“…We considered several individual background variables retrieved from the students' questionnaire and the measurement of competencies that were related to grade retention [9,14,50,[54][55][56][57]. Specifically, we retrieved information considering students' age, gender, immigrant background, language spoken at home, index of economic, social, and cultural status (derived from parents' highest level of education, parents' highest occupational status, and home possessions), home educational resources (i.e., household possessions and the number of books at home), and parents' emotional support (self-report measure where students where asked whether they feel supported by their parents) [53].…”
Section: Students' Social Background and Competenciesmentioning
confidence: 99%
“…We also integrated some school-related components as covariates considered in the literature related to grade retention [24,[54][55][56][57]. Specifically, we retrieved information regarding school type (public vs. private) [53].…”
Section: School Contextmentioning
confidence: 99%
“…In Spain, numerous schools have reported that they could not satisfy the current indoor environmental regulations and requirements for school buildings [79]. For instance, analyses of existing schools in Spain show that many of them do not meet the current sustainability requirements due to their conformity with old mechanisms, guidelines, and criteria [80,81]. These reports show that limitations on the budget and time of the construction processes are two main reasons for the aforementioned challenges.…”
Section: Introductionmentioning
confidence: 99%